2021
DOI: 10.1111/nous.12398
|View full text |Cite
|
Sign up to set email alerts
|

Ignore risk; Maximize expected moral value

Abstract: Many philosophers assume that, when making moral decisions under uncertainty, we should choose the option that has the greatest expected moral value, regardless of how risky it is. But their arguments for maximizing expected moral value do not support it over rival, risk-averse approaches. In this paper, I present a novel argument for maximizing expected value: when we think about larger series of decisions that each decision is a part of, all but the most risk-averse agents would prefer that we consistently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In contrast to this suggestion, numerous studies have shown that doctors’ own risk attitudes, rather than those of their patients, affect the clinical decisions they make 46–48. Meanwhile, in a parallel body of emerging literature about making risky decisions on behalf of others, which is not specific to medical contexts, philosophers adopt a range of positions about what risk attitude ought to be adopted 24 49–56…”
Section: Risk Attitudes and Deferencementioning
confidence: 99%
“…In contrast to this suggestion, numerous studies have shown that doctors’ own risk attitudes, rather than those of their patients, affect the clinical decisions they make 46–48. Meanwhile, in a parallel body of emerging literature about making risky decisions on behalf of others, which is not specific to medical contexts, philosophers adopt a range of positions about what risk attitude ought to be adopted 24 49–56…”
Section: Risk Attitudes and Deferencementioning
confidence: 99%
“… There are also explicit arguments in favour of a risk‐neutral version of EUT. In the moral context, see, for instance, Zhao (forthcoming). …”
mentioning
confidence: 99%